Differential Effects of Short-term Environmental Enrichment in Juvenile and Adult Mice. (1st March 2020) - Chandler, Kathleen; Dosso, Hosnia; Simard, Stephanie; Siddiqi, Sara; Rudyk, Chris; Salmaso, Natalina
Highlights: Short-term environmental enrichment decreases anxiety-like behaviour regardless of age. Enrichment increases rate of task acquisition in the Morris water maze in juvenile but not adult mice. Neural stem cells derived from juvenile brains show increased proliferation as compared to adults. Abstract: Environmental enrichment has been shown to increase cognitive abilities and accelerate recovery from a number of disease states. Typically, enrichment protocols last from four to eight weeks, however, it has previously been shown that two weeks of environmental enrichment is sufficient to increase cognitive abilities and the proliferation of the astroglial stem cell pool in juvenile mice. The current study examines whether a short-term enrichment protocol can induce similar effects in adults as compared to juveniles. Using juvenile and adult wild-type mice, we examined the effects of short-term environmental enrichment (including a running wheel) on cognitive abilities, anxiety-like behaviour, and the stem cell potential of sub-ventricular neural stem cells (NSC's) in vitro using neurosphere assays. We found that short-term environmental enrichment decreased anxiety behaviour and increased overall memory abilities similarly in juveniles and adults. However, the rate of acquisition on the Morris water maze, hippocampal Sox2 and Ki67 expression, and neurosphere potential increased in response to enrichment only in juveniles, suggesting that the effects of enrichment on these measures are age dependant. Together, these data suggest that the potential beneficial effects of environmental manipulations decrease with age.